Francesco da Barberino al crocevia Culture, società, bilinguismo - Bischetti, Sara; Montefusco, Antonio (Toscana Bilingue. Storia sociale della traduzione medievale / Bilingualism in Medieval Tuscany, 2021)
This volume presents an interesting case study dealing with the relationship between bilingualism and society in 14th-century Florence. Francesco da Barberino's Documenta Amoris are a sort of orthodox contrappunto of the Commedia, in which Dante's linguistic experimentation is substituted by Francesco's rigid bilingualism. The book provides one of the first interpretations of this fundamental figure of 14th-century Florentine culture.